The use of indwelling pleural catheters for the treatment of malignant pleural effusions. (3rd July 2019) - Syer, Tom; Walker, Steven; Maskell, Nick
ABSTRACT: Introduction : The presence of a malignant pleural effusion (MPE) is a marker of advanced disease and associated with a poor prognosis. Patients are in a palliative stage of their disease and often suffer distressing symptoms including breathlessness and pain. Indwelling pleural catheters (IPCs) are effective in managing pleural effusions and allow ambulatory drainage of the pleural space, reducing symptoms associated with effusions and lowering overall hospital stay. The role of IPCs as a first line option in managing MPEs is expanding with a multitude of recent studies into the optimal application of IPCs, necessitating a review of the current literature. Areas covered : This article will provide an overview of IPCs in MPE; how they're inserted, their indications, continuing management, complications and possible future applications. Expert opinion : IPCs should be considered first-line management of MPEs, alongside standard talc pleurodesis. Recognition of the advantages and disadvantages of each approach allows a more informed patient choice. It is recognized that the use of IPCs can provoke pleurodesis, leading to removal of the catheter. For patients in whom prompt removal of the catheter is a priority, then a more aggressive drainage regime or instillation of talc via the IPC is a reasonable option.